Experimental investigation on the viscosity of hybrid nanofluids made of two kinds of nanoparticles mixed in engine oil. (1st August 2018) - Liu, Yan; Yin, Deshun; Tian, Mingyuan; Hu, Xichen; Chen, Xuan
Abstract : To investigate the viscosity of hybrid nanofluids containing two kinds of nanoparticles, a series of experiments are conducted on TiO2 –Ag/engine oil, Al2 O3 –Ag/engine oil (a mixture of the volume ratio of 50:50) nanofluids under different shear rates and volume fractions. The results show that the viscosity decreases with increasing shear rate, which suggests TiO2 –Ag/engine oil and Al2 O3 –Ag/engine oil hybrid nanofluids are both shear thinning fluids, whilst the viscosity of all samples enhances with the increase of volume fraction. Moreover, an interesting result is observed that the hybrid nanofluids have a lower viscosity than single particle nanofluids. Also, through the validating experiment based on Al2 O3 –Al2 O3 /engine oil with different diameters, it shows that different materials with unlike morphologies mixture are more likely to reduce the viscosity than dissimilar nanoparticles mixture of just one material.